Sublime Gaps - Antoine Dechêne (Sillages Critiques)
This essay examines the ways in which metaphysical detective stories subvert one of detective fiction’s most emblematic features: the investigation’s resolution and the subsequent narrative closure. In the “The Man of the Crowd” (1840), the father of the genre, Edgar Allan Poe, already introduced mysteries that “[did] not permit [themselves] to be read.” Such texts enact quests for knowledge that cannot reach any kind of intellectual or emotional closure and are, instead, rewarded with more unfathomable questions. The sublime appears as a relevant concept to describe the “gaps” left open in the cognitive process of looking for answers, which will hopelessly remain beyond the detective’s — and the reader’s — reach. Including close readings of Henry James’s “The Figure in the Carpet” (1896) and Samuel Beckett’s Molloy (1951), this essay proceeds to show that the “metaphysical” character of these texts lies predominantly in their lack of faith in language as a reliable tool to convey the multiple and shifting identities of the unsuccessful sleuth confronted with the meaninglessness of his investigation.